Interventions that prevent or reduce perinatal loneliness and its proximal determinants: a restricted scoping review - Ruth Naughton-Doe; Rebecca Nowland; Stephanie Tierney; Martin Webber; Anja Wittkowski (BMC Public Health)
Abstract Background The World Health Organisation’s Commission on Social Connection (2024–2026) highlights the importance of addressing loneliness because of its negative impact on health and well-being. The perinatal period carries an increased risk of loneliness for mothers and fathers which is elevated by intersectional inequalities, such as having a low income, being LGBTQ+, or being from a minoritised community. Perinatal loneliness is associated with perinatal mental illness, which can have lasting negative impacts on parents and their children. The aim of this review was to synthesise studies exploring interventions for perinatal loneliness. Methods We conducted a restricted scoping review following the Joanna Briggs Institute Methodology to develop a categorisation of interventions and intervention-mechanisms to reduce perinatal loneliness. We included studies that described and/or evaluated interventions in published studies that intentionally or unintentionally reduced loneliness, or its proximate determinants, such as social connectedness and social support. We searched eight electronic databases for peer-reviewed academic papers published in any country describing or evaluating these interventions between 2013–2023. Results Fifty papers were included in the review, from which the following categorisation of interventions was developed: 1) synthetic social support, 2) shared-identity social support groups, 3) parent and baby groups, 4) creative health approaches (arts, nature or exercise based), 5) holistic, place-based and multidisciplinary support that worked with parents to overcome a range of barriers to connection, and 6) awareness campaigns. Five mechanisms were identified within included papers: 1) opportunities for social connection to similar others, 2) positive relationships with a professional or volunteer, 3) normalisation and acceptance of difficulties, 4) meaningful activities and 5) support to overcome barriers (including cultural and financial) to connection. Few studies collected comprehensive demographic data, few considered fathers, and none were LGBTQ+ specific. Conclusions The review identified and synthesised approaches that might address perinatal loneliness and its proximate determinants. Further research is needed to scope the grey literature, review papers in the global south, appraise intervention effectiveness, and co-produce interventions, including for fathers, LGBTQ+ parents, and cultural and religious minorities. Trial registration The protocol for the trial was registered on Figshare.